2019
DOI: 10.1093/scan/nsz061
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates for anticipation and consumption of social and monetary incentives in depression

Abstract: Depression has been reliably associated with abnormalities in the neural representation of reward and loss. However, most studies have focused on monetary incentives; fewer studies have considered neural representation of social incentives. A direct comparison of non-social and social incentives within the same study would establish whether responses to the different incentives are differentially affected in depression. The functional magnetic resonance imaging study presented here investigated the neural acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 81 publications
4
32
0
Order By: Relevance
“…Fourth, the cut-off date the studies that were included in our meta-analyses were identified was about 2 years ago, which raises the question of whether our meta-analyses might be missing a considerable number of fMRI studies using the SID task published in the past 2 years. To address this concern, we conducted a new literature search on 17/04/2020 which identified only a single study meeting our inclusion/exclusion criteria (He et al, 2019). We are thus confident that our metaanalyses still represent the vast majority of the published studies in this field.…”
Section: Limitationsmentioning
confidence: 99%
“…Fourth, the cut-off date the studies that were included in our meta-analyses were identified was about 2 years ago, which raises the question of whether our meta-analyses might be missing a considerable number of fMRI studies using the SID task published in the past 2 years. To address this concern, we conducted a new literature search on 17/04/2020 which identified only a single study meeting our inclusion/exclusion criteria (He et al, 2019). We are thus confident that our metaanalyses still represent the vast majority of the published studies in this field.…”
Section: Limitationsmentioning
confidence: 99%
“…It remains undetermined if a unified neural mechanism underlies both social and nonsocial decision-making. Many researchers believe that regardless of whether a social component is involved, different kinds of decision-making are driven by identical neural value computations and corresponding brain processes [84,[97][98][99]. For example, the ventral striatum (a key node within the dopaminergic midbrain system) is sensitive to both monetary reward and social approval [100].…”
Section: Pain and Social Decisionsmentioning
confidence: 99%
“…The latter findings highlighted complex effects of individual reward sensitivity on cognitive performance incentivized by monetary reward. Investigators have also associated sensitivity to punishment with higher insula activity during feedback of social loss in a social incentive delay task in people with subthreshold depression [ 44 ]. On the other hand, despite its wide use in the imaging literature, no studies of the monetary incentive delay task (MIDT) have examined how neural responses to monetary wins or losses may vary with individual sensitivity to reward or to punishment.…”
Section: Introductionmentioning
confidence: 99%